Stress and Its Impact on Principal Performance: An Overview of Education Management - Ulfiah, Ulfiah; Nurannisa, Anti; Firdausi, Fanida (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2022)
This study aims to determine the impact of stress felt by school principals at the elementary school level in Bandung Regency. The research uses qualitative methods with a phenomenological approach. The research was conducted in January 2022 for three weeks through in-depth interviews with three informants. The purposive sampling technique selected informants. Data analysis was carried out by content analysis and triangulation of sources and methods. The results show that an unhealthy work environment pressure from teachers can affect the performance of school principals regardless of gender. Stress that can be felt in headaches, body aches, and hypertension are the main symptoms felt. This research implies that the principal looks moody or often emotional because he feels stressed at work and feels symptoms of illness. It is recommended that principals hire competent employees to assist in administration, delegate tasks, hold regular meetings and counseling, reduce their stress and create a supportive environment for a more efficient school administration.